The Effect of Profitability and Liquidity on Firm Value with Financial Distress as a Mediating Variable - Arief, Harefan; Oktaviar, Chairiel; Saratian, Eko Tama Putra; Soelton, Mochamad; Yuliantini, Tine (Universitas Mercu Buana, 2024)
Financial distress is a phase that precedes the state in which a business faces incapacity or failure, which can even lead to bankruptcy. If a company experiences a lack of funds for internal financing, a solution can be found by utilising debt as a source of external funding from other parties. Business failure and the risk of bankruptcy are often fears in a competitive business environment. Financial distress arises when a company is unable to fulfil its payment obligations or repay its debts. For internal companies, bankruptcy analysis is useful as an early warning against potential bankruptcy, providing an opportunity to maintain business continuity or sustainability. Therefore, the risk of bankruptcy can be minimised through proper analysis, allowing for a quick improvement. Some commonly used models to analyse corporate financial distress include the Altman, Springate, and Zmijewsk models. This study aims to analyse and identify the influence of fundamental factors represented by ratios, such as ROA Ratio, Current Ratio, and Firm Value, on the condition of Financial Distress in mining sector stocks on the Indonesia Stock Exchange. The research will focus on the impact of Profitability and Liquidity on Firm value, with Financial Distress as a mediating variable.The research results can be described as follows ROA has no effect on Firm Value. Current Ratio has no effect on Firm Value. ROA has no effect on Financial Distress. Current Ratio has a positive and significant effect on. Financial Distress, Financial Distress has a significant positive effect on Firm Value. Financial distresscannot mediate the relationship of Profitability (ROA) to Firm Value. Financial distress cannot mediate the relationship of Liquidity (Current Ratio) to Firm Value.